The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.bbadis.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Altered feeding differentially regulates circadian rhythms and energy metabolism in liver and muscle of rats

Abstract: Energy metabolism follows a diurnal pattern responding to the light/dark cycle and food availability. This study investigated the impact of restricting feeding to the daylight hours and feeding a high fat diet on circadian clock (bmal1, dbp, tef and e4bp4) and metabolic (pepck, fas, ucp3, pdk4) gene expression and markers of energy metabolism in muscle and liver of rats. The results show that in chow-fed rats switched to daylight feeding, the peak diurnal expression of genes in liver was shifted by 6-12h while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 47 publications
4
69
1
1
Order By: Relevance
“…Indeed, we have observed that forced synchronization of food intake prevents obesity and allows recover reward performance [26,37,48]. Otherwise, mismatch between feeding and light/dark cycle has been shown to disrupt energy metabolism in skeletal muscle and has significant consequences for whole-body energy homeostasis [49].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have observed that forced synchronization of food intake prevents obesity and allows recover reward performance [26,37,48]. Otherwise, mismatch between feeding and light/dark cycle has been shown to disrupt energy metabolism in skeletal muscle and has significant consequences for whole-body energy homeostasis [49].…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were resolved by SDS-PAGE electrophoresis, and immunoblot analysis was conducted as described elsewhere [19,24,25]. Immunolabelled bands were quantified using ImageJ 1.44p software.…”
Section: Methodsmentioning
confidence: 99%
“…In a study on a mouse model of shift work, restoring normal food intake rhythms concurrently restores clock gene rhythmicity in the liver, as well as triglyceride, glycerol and GC rhythms, and gluconeogenesis (Barclay et al 2012). While these data suggest a direct link between peripheral clock regulation and energy homeostasis, the phase relationship between clock gene expression and the transcriptional activity of metabolismassociated genes is variable, suggesting an interplay between local and systemic factors (Reznick et al 2013). …”
Section: Ghrelin and Insulinmentioning
confidence: 99%